Co-building trust in urban nature: Learning from participatory design and construction of Nature-Based Solutions in informal settlements in East Africa - Diep, Loan; Mulligan, Joe; Oloo, Martha Akinyi; Guthmann, Loė; Raido, Mussa; Ndezi, Tim (Frontiers in Sustainable Cities, 2022)
While the amount of research on NBS is growing rapidly, there is a lack of evidence on community experiences of NBS design and implementation, particularly from low-income and informal settlements of African cities. This article adds new empirical evidence in this space through grounded analysis of NBS “niche” projects co-developed by “intermediary” organizations and communities in five sites across three settlements in Nairobi and Dar es Salaam. Findings are organized around four established NBS knowledge gaps: 1) NBS-society relations; 2) design; 3) implementation; 4) effectiveness. We find that across the five studied sites, residents’ perceptions and valuation of urban nature has changed through co-design and co-implementation, enabling community ownership of projects, and hence playing a crucial role in NBS effectiveness over time. The integration of gray components into green infrastructure to create hybrid systems has proven necessary to meet physical constraints and communities’ urgent needs such as flood mitigation. However, maintenance responsibilities and cost burdens are persisting issues that highlight the complex reality of NBS development in informal settlements. The cases highlight key considerations for actors involved in NBS development to support the replication, scaling up and institutionalization of NBS. These include the need to: i) develop forms of engagement that align with co-production approaches; ii) capture communities’ own valuation of and motivations with NBS development for integration into design; iii) elaborate technical guidance for hybrid green-gray infrastructure systems that are co-constructed with communities; and iv) help define and establish structures for maintenance responsibilities (especially governmental versus civil society) that will enhance the environmental stewardship of public spaces.